Application of Canola Oil Biodiesel/Diesel Blends in a Common Rail Diesel Engine - Jun Cong Ge; Sam Ki Yoon; Min Soo Kim; Nag Jung Choi (Applied Sciences, 2016)
In this study, the application effects of canola oil biodiesel/diesel blends in a common rail diesel engine was experimentally investigated. The test fuels were denoted as ULSD (ultra low sulfur diesel), BD20 (20% canola oil blended with 80% ULSD by volume), and PCO (pure canola oil), respectively. These three fuels were tested under an engine speed of 1500 rpm with various brake mean effective pressures (BMEPs). The results indicated that PCO can be used well in the diesel engine without engine modification, and that BD20 can be used as a good alternative fuel to reduce the exhaust pollution. In addition, at low engine loads (0.13 MPa and 0.26 MPa), the combustion pressure of PCO is the smallest, compared with BD20 and ULSD, because the lower calorific value of PCO is lower than that of ULSD. However, at high engine loads (0.39 MPa and 0.52 MPa), the rate of heat release (ROHR) of BD20 is the highest because the canola oil biodiesel is an oxygenated fuel that promotes combustion, shortening the ignition delay period. For exhaust emissions, by using canola oil biodiesel, the particulate matter (PM) and carbon monoxide (CO) emissions were considerably reduced with increased BMEP. The nitrogen oxide (NOx) emissions increased only slightly due to the inherent presence of oxygen in biodiesel.